2017
DOI: 10.3329/bjms.v16i2.31944
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Semen Analysis: Experiences of a Laboratory Catering to Semi Urban Population of Delhi

Abstract: Abstract:Background:Infertilityis defined as failure of a couple to conceive after one year of regular sexual intercourse. It remains both prevalent and problematic among couples worldwide. The analysis of semen remains the preliminary investigation for males in the workup of infertility in couples.It is a key element in the fertility evaluation of men and permits male reproductive potential to be evaluated in association with possible risk factors. Aim: To assess and analyse the semen characteristics of all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 10 publications
3
15
0
Order By: Relevance
“…The mean percentage of normal motile sperms was 57% ± 9.76 in normospermia samples as compared to oligospermia in which motile sperms were 28% ± 10%. In our study, asthenozoospermia was observed in 28% of samples and comparable results were obtained from a studies conducted by Butt et al 5 (25.81%) and Aulia et al 6 (22.1%), while much lower percentage is reported by Jarajpuri et al 15 (5.9%), Ramya et al 16…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The mean percentage of normal motile sperms was 57% ± 9.76 in normospermia samples as compared to oligospermia in which motile sperms were 28% ± 10%. In our study, asthenozoospermia was observed in 28% of samples and comparable results were obtained from a studies conducted by Butt et al 5 (25.81%) and Aulia et al 6 (22.1%), while much lower percentage is reported by Jarajpuri et al 15 (5.9%), Ramya et al 16…”
Section: Discussionsupporting
confidence: 91%
“…Our study revealed azoospermia in 28 (7.6%) of males, which was comparable to study by Jairajpuri et al from Delhi in which azoospermia was 9% 15 and Ramya et al reported 7.5%.16 Much lower percentage was reported by Anuja et al from Devanahalli as 2%. 17 One of the Pakistani study by Fouzia et al shows Azoospermia to be 14.89%.…”
Section: Discussionsupporting
confidence: 85%
“…This is a very rarely seen abnormality in our country. 11,16,[31][32][33][34][35][36][37] The infertility rate we observed is compared to that reported by different authors from different parts of globe (Table 3).…”
Section: Discussionmentioning
confidence: 93%
“…Delhi being highly polluted may be responsible for poor semen in 84% of total cases. 34 In this retrospective study where semen records were scrutinized and 62% of them were infertile. Some of their partners may also be infertile, and which is not known and is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation